If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+7=5x-3(x-4)
We move all terms to the left:
2x+7-(5x-3(x-4))=0
We calculate terms in parentheses: -(5x-3(x-4)), so:We get rid of parentheses
5x-3(x-4)
We multiply parentheses
5x-3x+12
We add all the numbers together, and all the variables
2x+12
Back to the equation:
-(2x+12)
2x-2x-12+7=0
We add all the numbers together, and all the variables
-5!=0
There is no solution for this equation
| 10+x/4=22 | | 1x/2-9=7.5+6x | | -24=-4(2x-4) | | -11c+12c—15c-3c=-13 | | X^2+3+2x+4=15 | | 3x+216=2x | | k-3=7/9 | | 8k+4=8k | | 3(x+2(=-3x+6 | | -16+2=-2(x+8) | | 4(x+3)+10(x-3)=10 | | 4x=-8x+12 | | 6=(5+2x)(0.6) | | 6(2x+2)=4(3x-5) | | 46t-23=46t+23 | | 1/2(-3x^2-x)=0 | | 5p+8=6p | | |5x|=40 | | 45=12a-3 | | 4y+32=-3(y-6) | | 9x-27=-90 | | -7+x/3=-14 | | 3x+12-30=180 | | 2(a+3)=3(6a+2) | | x+1+2x-2=x+4 | | 6=(5+2x)(0.2) | | -4x+5x=-2 | | -12t+5=1+8t-20t | | (5x-2)+(4x+1)+(x+23)=122 | | 6+4(m-5)=10 | | 4.67-y+y=y-1.2 | | x/6-7=-14 |